2022
DOI: 10.2147/jir.s370085
|View full text |Cite
|
Sign up to set email alerts
|

Preprocedural SII Combined with High-Sensitivity C-Reactive Protein Predicts the Risk of Contrast-Induced Acute Kidney Injury in STEMI Patients Undergoing Percutaneous Coronary Intervention

Abstract: Objective To investigate the relationship between the incidence of contrast-induced acute kidney injury (CI-AKI) and the levels of the systemic immune-inflammatory index (SII, platelet × neutrophil/lymphocyte ratio) and high-sensitivity C-reactive protein (hsCRP) in patients with ST-segment elevation myocardial infarction (STEMI) undergoing percutaneous coronary intervention (PCI), to analyze further the predictive value of the combination of SII and hsCRP for CI-AKI. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
0
2
0
Order By: Relevance
“…An analysis of 11 studies showed a moderate diagnostic value of IL-18 [ 71 ]. Other inflammatory markers such as the systemic immune-inflammatory response index (SII) and high-sensitivity C-reactive protein (hsCRP) may also prove useful [ 72 , 73 ]. These new biomarkers can aid risk stratification, early detection and early intervention in case of AKI in patients with AMI.…”
Section: New Markers Of Kidney Damagementioning
confidence: 99%
“…An analysis of 11 studies showed a moderate diagnostic value of IL-18 [ 71 ]. Other inflammatory markers such as the systemic immune-inflammatory response index (SII) and high-sensitivity C-reactive protein (hsCRP) may also prove useful [ 72 , 73 ]. These new biomarkers can aid risk stratification, early detection and early intervention in case of AKI in patients with AMI.…”
Section: New Markers Of Kidney Damagementioning
confidence: 99%
“…Lian et al also supported that the decline in ADL resulted in the upregulation of inflammatory markers [35] . Inflammatory markers upregulation, involving C-Reactive Protein (CRP), etc., is closely related to the occurrence of CA-AKI [36,37] . In the current research, the predictive value of BI score on the occurrence of CA-AKI was still observed after adjustment for these well-established risk factors.…”
Section: Resultsmentioning
confidence: 97%
“…The literature contains little information on the relationship between the SII and short-term mortality in SA-AKI [25]. Academic efforts have primarily focused on the prognostic potential of SII in disease onset prediction [11,26,27]. Studies indicate higher SII levels among SA-AKI cohorts compared to non-AKI groups.…”
Section: Discussionmentioning
confidence: 99%